Effect of Decoquinate on gain and health of newly-arrived stocker cattle - Brazle, F. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Decoquinate (Deccox®), when added to the diet of newly-arrived calves, reduced (P<.05) the number of treatments required per animal in three experiments involving 551 cattle. Feed conversion was improved in two of the three experiments and average daily gain was increased (P<.05) in one experiment when Deccox® was fed. Steer calves gained faster (P<.001) and required fewer (P<.01) treatments per head than bulls calves castrated on arrival. Black, medium-framed calves required fewer (P<.05) treatments than other breed types.
Keywords: Beef; Decoquinate (Deccox®); Gain; Health; Stocker cattle